Solidaritas Sosial Pengurus Persatuan Pedalangan Indonesia (Pepadi) Sultra di Kota Kendari - Jumaria Jumaria; Abdul Jalil; Wawan Cahyadin (JURNAL KABANTI: Kerabat Antropologi, 2023)
The Association of Indonesian Puppeters (PEPADI) Southeast Sulawesi is one of the Javanese arts organizations located in Southeast Sulawesi or in Kendari City, in this organization it is not only focused on Wayang Kulit art but also widens other affairs and uniquely when this organization runs, the solidarity is also wake up. This study aims to identify and describe the forms of social solidarity that exist in the PEPADI Sultra Management in Kendari City. The data collection technique used in this study is a field research technique using two methods, namely observation and interviews.This research was conducted using qualitative methods. The results of this study indicate that the forms of Social Solidarity that exist in the PEPADI Sultra Management are formed because of the similarity of taste, namely living together in overseas lands, by forming monthly social gatherings and also working together in weddings, thanksgiving and mourning not only that PEPADI Sultra also cooperation with the Javanese tribal community in the success of the Javanese cultural arts performance held in Kendari City, Southeast Sulawesi. In maintaining this solidarity, the role of the chairman of PEPADI Sultra is to continue to protect its members so that they remain solid, and share the same fate, as well as the philosophy or way of life of the Javanese in their daily life.